Positron Annihilation Lifetime Spectroscopy in the study of defects in materials - Triantou, K.; Mergia, K.; Stamatelatos, I. E. (HNPS Advances in Nuclear Physics, 2019)
The Positron Annihilation Lifetime Spectroscopy (PALS) is a valuable method for the study of the open volume defects in materials. The reduced electron density at the vacant/defect site increases the positron lifetime, and positron lifetime increases as the size of defect increases. In the current paper the experimental apparatus for the measurement of the positron lifetime in materials is described and the spectra from W and Cd specimens are analyzed. The presence of dislocations and vacancy defects is found, since the positron lifetimes of specimens are higher than the defect-free (bulk) values.